PERAN EMBUNG TERHADAP INDEKS PERTANAMAN PADI DAN FAKTOR YANG MEMPENGARUHI PRODUKSI PADI (STUDI KASUS LOKASI EMBUNG KABUPATEN BOGOR, JAWA BARAT) - Nardi Nardi; Achmad Tjachja Nugraha; Iwan Aminudin (BUANA SAINS, 2021)
Rice production in Bogor Regency has fluctuated and tends to fall, even though almost 70-80% of technical irrigated land with rainfall is relatively stable per year and higher than its surroundings, but the availability of water for rice plants is unstable. This research aimed to analyze the difference in Planting Index (IP) before and after embung in the research location and the role of the reservoir factor in increasing rice production in the research location. This research was approached using quantitative descriptive in a case study at the Embung location, Bogor Regency. Furthermore, the difference between the planting index (IP) of rice before and after embung was examined with the non-parametric Wilcoxon signed-rank test to determine there is a role for embung factor in increasing rice production using multiple linear regression analysis (F test and t-test). The result showed that there is a significant difference in the Planting Index (IP) before and after embung at the research location based on the non-parametric Wilcoxon signed-rank test, with the Asymp value. Sig 0.009 0.05 (α = 0.5%) or the level of confidence 95%, then there is a role for embung variable factor on the increase in production at the research location based on multiple linear regression analysis, either simultaneously (F test) or partially (t-test). significant to the rice production variable with a significance value less than 0.05 (α = 0.5%) or a confidence level of 95%.